Evaluation of the accumulation of the iodinated contrast agents diatrizoic acid and iohexol in Dreissena polymorpha mollusks. (January 2023) - Daniele, Gaëlle; Lafay, Florent; Arnaudguilhem, Carine; Mounicou, Sandra; Geffard, Alain; Bonnard, Isabelle; Dedourge-Geffard, Odile; Bonnefoy, Christelle; Vulliet, Emmanuelle
Abstract: Mollusks are very sensitive to aquatic environmental alterations and then, are important bio-indicators for monitoring the contamination of water bodies. Iodinated X-ray contrast media (ICMs) are ubiquitously present in the aquatic environment, primarily due to their high consumption for diagnosis purposes, high injection levels, low biodegradability, and low removal rates by wastewater treatment plants. Although these compounds are assumed to be of low toxicity, aquatic organisms are continuously exposed to these agents, which may result in adverse effects as ICMs can act as iodine source and disrupt the endocrine system. Thus, the evaluation of their environmental risk, especially on aquatic fauna is of great interest. To this end, we first compared the accumulation behavior, based on iodine analysis, of two ICM exhibiting different osmolality, diatrizoic acid and iohexol in Dreissena polymorpha bivalves exposed under laboratory conditions at concentrations of 0, 100, and 1000 μg/L during 4 and 7 days. This study was the first to provide information on iodine concentration in whole soft tissues and several organs in control zebra mussels. Moreover, it showed, after exposure, an increase of iodine content mainly in the digestive glands, followed by gills and gonads, highlighting that ICMs actually enter the organisms. Thus, bioaccumulation of ICMs studies were then performed, by liquid chromatography coupled to tandem mass spectrometry, on entire mollusks and digestive glands of organisms exposed at 0, 10, 100, and 1000 μg/L of both ICMs during 21 days, followed by 4 days of depuration. These first data on ICMs concentrations in zebra mussels, showed a clear accumulation of ICMs in mussels as a function of relative exposure level, as well as a rapid depuration. Osmolality did not seem to have a significant impact on the accumulation level, but a slight difference was observed on the accumulation pattern between both ICMs. Graphical abstract: Image 1 Highlights: Basal iodine level is determined in organs of D. polymorpha bivalves for the first time. Iodine concentration increases in different bivalve's tissues due to ICMs exposure. Iodine accumulation is highest in the digestive glands. For the first time the entering of ICMs in bivalves is demonstrated. DTZ and IO both accumulate in bivalve whole tissues and digestive glands.